PENGARUH DISIPLIN TERHADAP KINERJA KARYAWAN PADA KOPERASI SIMPAN PINJAM (KSP) WAGURA LAMPUNG TIMUR - Buchori Buchori (DINAMIKA: Jurnal Manajemen Akuntansi, Bisnis dan Kewirausahaan, 2018)
A company can not be separated from human resources even though the company has a large capital and modern technology. The success of a company is determined by employee performance. One of the factors that can affect employee performance is discipline. The formulation of the problem in this research is whether there is influence of discipline on employee performance in KSP Savings and Credit Cooperatives. Wagura Way Jepara, East Lampung? The purpose of this study was to determine the effect of discipline on employee performance in KSP Savings and Credit Cooperatives. Wagura Way Jepara, East Lampung. This research is descriptive research with quantitative analysis. Data collection techniques in this research are documentation and questionnaire. The population is all employees in KSP Wagurayang numbering 10 people. Samples of as many as 10 people or all Wagura KSP employees. Data analysis techniques using simple linear regression analysis with the help of SPSS 21. The results of this study are the significant value of Discipline is 0.002, the value is smaller than 0.05 so that the Hypothesis (Ha) which states "There is Discipline Influence on Employee Performance in the Wura KSP Savura Loan Cooperative in East Lampung 2019" can be accepted. R square value or the coefficient of determination = 0.594, which means the effect of Discipline on employee performance is 59.4%, and the rest is influenced by other factors not examined in this study